Dampak Fundamental Perusahaan terhadap Return Saham Perusahaan Telekomunikasi Milik Negara - Arniwita Arniwita; Endah Tri Kurniasih; Ermaini Ermaini; Mustika Mustika (J-MAS (Jurnal Manajemen dan Sains), 2022)
Investments in the telecommunications industry are the most sought after options by investors as a result of the use of digital in various activities today. The main focus in this study is to analyze how the performance of the company's financial ratios influences the stock returns of telecommunication companies listed on the Indonesia Stock Exchange. The research method used is descriptive quantitative with multiple linear regression analysis tools. The data in this study are secondary data sourced from the annual reports of telecommunications companies listed on the Indonesian Stock Exchange, namely PT. Telekomunikasi Indonesia Tbk, 2019-2021 period and statistical data on the Indonesia Stock Exchange (IDX). The results showed that the performance of the company's fundamental ratios, namely net profit margin, earnings per share, and price to book value fluctuated annually from 2019 to 2021. Based on the results of the data analysis, it was found that the company's fundamental performance had a significant effect on returns. company shares with a significance level of 5%. Furthermore, the results show that earnings per share (EPS) has no effect on stock returns of PT. Telekomunikasi Indonesia Tbk.